Effect of contact force on pulsed field ablation lesions in porcine cardiac tissue. (20th January 2023) - Mattison, Lars; Verma, Atul; Tarakji, Khaldoun G.; Reichlin, Tobias; Hindricks, Gerhard; Sack, Kevin L.; Önal, Birce; Schmidt, Megan M.; Miklavčič, Damijan; Sigg, Daniel C.
Abstract: Introduction: Contact force has been used to titrate lesion formation for radiofrequency ablation. Pulsed field ablation (PFA) is a field‐based ablation technology for which limited evidence on the impact of contact force on lesion size is available. Methods: Porcine hearts ( n  = 6) were perfused using a modified Langendorff set‐up. A prototype focal PFA catheter attached to a force gauge was held perpendicular to the epicardium and lowered until contact was made. Contact force was recorded during each PFA delivery. Matured lesions were cross‐sectioned, stained, and the lesion dimensions measured. Results: A total of 82 lesions were evaluated with contact forces between 1.3 and 48.6 g. Mean lesion depth was 4.8 ± 0.9 mm (standard deviation), mean lesion width was 9.1 ± 1.3 mm, and mean lesion volume was 217.0 ± 96.6 mm 3 . Linear regression curves showed an increase of only 0.01 mm in depth (depth = 0.01 × contact force + 4.41, R 2  = 0.05), 0.03 mm in width (width = 0.03 × contact force + 8.26, R 2  = 0.13) for each additional gram of contact force, and 2.20 mm 3 in volume (volume = 2.20 × contact force + 162, R 2  = 0.10). Conclusion: Increasing contact force using a bipolar, biphasic focal PFA system has minimal effects on acute lesion dimensions in an isolated porcine heart model and achieving tissue contact is more important than the force with which that contact is made. Abstract : Using an isolated swine heart model, a focal ablation catheter was used to apply pulsed electrical fields with varying contact forces as well as with a 2 mm offset (catheter 2 mm away from tissue, not touching). Increasing contact force using a bipolar, biphasic focal PFA system has minimal effects on acute lesion dimensions in an isolated porcine heart model and achieving tissue contact is more important than the force with which that contact is made.